The Effect of Training and Development on Employee Engagement in the Process of Online Learning at Child Development center, Bandung Jakarta - Alive, Aditya; Sya’roni, Deden Abdul Wahab (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Training is the process of teaching the basic skills needed by employees to do work, which is then followed by career development that can have a positive impact on both employees and the company. This study aims to determine the effect of training and development on Employee Engagement in the learning process at the Indonesian compassion children development center in the Bandung Jakarta cluster during the Covid-19 pandemic, where each employee must adjust to a different learning process from before with new ones that must be mastered to ensure the online learning process is carried out optimally. This study uses a qualitative descriptive analysis. By processing and analyzing data, and describing the data that has been collected in general. The results of this study from this study indicate development and training can increase employee engagement to the company / organization because the needs of employees are met as well as the high emotional and intellectual relationships that employees have. to their work, organization, manager, or co-workers who have an influence to increase discretionary effort in their work